Farmers' Ability in Estrus Detection and Mating Time Determination For Moa Buffalo Cows In Moa District, Southwest Maluku Regency - Ismael Kewilaa, Arnold; Lewan Dolewikou, Risart; Gairtua, Barnabas; Sairudy, Albertus; Harmoko, Harmoko (Sahabat Publikasi, 2025)
The purpose of this study was to determine the ability of breeders in the detection of heat and determination of mating time in Moa buffalo mothers in Moa District, Southwest Maluku Regency. This research is planned to take place for 1 month from September to October 2024 in Moa District, Southwest Maluku Regency. Determination of sample villages by purposive sampling by considering the density of buffalo population and in accordance with the geographical villages/hamlets on Moa island, namely the western region (Pati and Werwaru villages), the central region (Klis and Nyama villages), and the eastern region (tounwawan and Poliwu). The number of respondents interviewed was 60 people. Data collection was carried out by interview. Respondents were selected through purposive sampling with the criteria of having at least 3 female buffaloes and at least 1 male and having been in the business for more than 5 years. Observational variables included: breeder's ability to detect lambing, post partum mating timing, and mother productivity including: age at first mating, pregnancy rate, birth rate, post partum mating and preweaning mortality. The data obtained were tabulated, analyzed using descriptive statistical analysis by calculating the percentage, average and standard deviation. The results showed that 58.33% of farmer respondents in Moa Sub-district, Southwest Maluku Regency had knowledge and ability in the moderate category in detecting lambing, 40.00% of farmers had knowledge and ability in the low category, and 1.67% of farmers had knowledge and ability in the good category. 100% of farmer respondents in Moa Sub-district, West Maluku District did not have the knowledge and ability to determine the right mating time after parturition. The potential productivity of Moa buffalo mothers is as follows: age at first mating 37.17 ± 2.42 months, pregnancy rate 77.20%, birth rate 97.66%, post partum mating 12.47 ± 0.85, and preweaning mortality 19.76%.